(untitled) (Società e diritti, 2022)
The essay focuses on the relationship between personalism and solidarity in contract law, the roots of which can be found in the prophetic and still current reflections of Giuseppe Toniolo. In particular, it is highlighted how the protection of the weak part of the relationship, according to a principle of substantial equality, leads to the creation of an economic market system based on respect for the dignity of the human person.